Strategi pembangunan pariwisata internasional berbasis pertanian organik “shining batu” - Yusuf Adam Hilman (Universitas Muhammadiyah Ponorogo, 2017)
Natural potential and also local knowledge possessed by Batu, a great asset that can be implied to improve the welfare of the community, through the program